2013
DOI: 10.1371/journal.pone.0061339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spatial Separation of Pigs on Spread of Streptococcus suis Serotype 9

Abstract: The spread of an infectious agent in a population can be reduced by interfering in the infectiousness or susceptibility of individuals, and/or in their contact structure. The aim of this study was to quantify the effect of prevention of direct contact between infectious and susceptible pigs on the transmission of Streptococcus suis (S. suis). In three replicate experiments, S. suis-free pigs were housed in boxes either in pairs (25 pairs) or alone (15 pigs). The distance between the boxes was ±1 m. At 7 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 47 publications
6
41
0
Order By: Relevance
“…The presence of S. suis in the air of SCB confirms their findings and the data of Berthelot-Herault (35) and showed that spatial separation of animal groups within a compartment would not prevent S. suis transmission on a farm (59). In Canada, the United States, and Europe at this time, S. suis infections in humans have most often been restricted to workers in close contact with pigs or contaminated swine products.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The presence of S. suis in the air of SCB confirms their findings and the data of Berthelot-Herault (35) and showed that spatial separation of animal groups within a compartment would not prevent S. suis transmission on a farm (59). In Canada, the United States, and Europe at this time, S. suis infections in humans have most often been restricted to workers in close contact with pigs or contaminated swine products.…”
Section: Discussionsupporting
confidence: 77%
“…Dekker et al determined that prevention of direct contact with infected animals decreases the risk of infection in susceptible pigs (59). The presence of S. suis in the air of SCB confirms their findings and the data of Berthelot-Herault (35) and showed that spatial separation of animal groups within a compartment would not prevent S. suis transmission on a farm (59).…”
Section: Discussionmentioning
confidence: 84%
“…The proportion of infected pigs at 6 weeks later is presented while raising the litters separated or randomly mixed after weaning (with 95% percentiles). (Dekker et al, 2013) and several viral pathogens (e.g. Classical Swine Fever virus (Klinkenberg et al, 2002), Footand-Mouth disease virus (Eblé et al, 2006) and Porcine circovirus (PCV2) (Andraud et al, 2008)).…”
Section: Discussionmentioning
confidence: 99%
“…Modeling the travel as a random walk, i.e., diffusion in 2D space (and including the decay of the pathogen while traveling), has the advantage that it explains both the delay and the difference in delay between the two bacterium species. Modeling it only as a buildup in the environment without a spatial component (16) would not explain the difference in delay. Although in our current model the diffusion is precisely following a 2D diffusion equation, this might not necessarily be the case; the movement of the infectious material in space does not have to be a random walk as we assumed.…”
Section: −1mentioning
confidence: 99%